Maqashid Al-Syari’ah Dalam Kajian Teoritik Dan Praktek - Sarah, Siti; Isyanto, Nur (Tasyri' : Journal of Islamic Law, 2022)
Maqashid al-Shari'ah is an alternative in an effort to solve socio-religious problems in the current era. This is because it is realized that the texts, both the Qur'an and Hadith as the main sources of Islamic law, are very limited in number while social problems continue to emerge one after another. The purpose of this paper is to describe the concept of maqashid al-syari'ah both at the theoretical level and in its application. This study is included in the category of library research by utilizing data or information from ushul fiqh books as a primary source, then assisted by some information obtained from journals, other relevant books as secondary sources. The data obtained were described and then analyzed. This paper finds that: 1) maqashid al-syar'iah is part of qa'idah ushuliyyah and also approaches in understanding the texts of the Qur'an and the Prophet's Hadith. 2) Mujtahids must understand maqashid al-syariah in an effort to capture and interpret the divine verses hidden behind their textual folds. 3) Maqashid al-Sharia as an approach, needs to be refreshed and rearranged according to the current context.